KEMAMPUAN KOMUNIKASI MATEMATIK SERTAKEMAMPUAN DAN DISPOSISI BERPIKIR KRITIS MATEMATIK - Hendriana, Heris; Sumarmo, Utari; Rohaeti, Euis Eti (Delta-Pi: Jurnal Matematika dan Pendidikan Matematika, 2013)
This studyis a post test experimental control group design conducted in 2013by using Problem Based Learning (PBL)to investigate students? mathematical communication,mathematicalcritical thinking abilityand disposition. The study involves 76 students of grade-11 from a senior high school in Cimahi. The study employs three kinds of instrument namely mathematical communication and mathematical critical thinking tests and mathematical critical thinking scale. The study found that the grade of mathematical communication ability of students taught by PBL was classified as fairly good and it was better than the grade of students taught by conventional teaching that classified as medium. However, there was no different grades of mathematical critical thinking ability and of disposition of students in the both classes. The grades of mathematical critical thinking of students were classified as medium, and the grades of mathematical critical thinking disposition of students were classified as fairly good.  The other findings there were not association among mathematical communication,critical thinking abilities and mathematicalcritical thinkingdisposition.